Being ethically minded: Practising the Scholarship of Teaching and Learning in an ethical manner - Healey, Ruth L.; Bass, Tina; Caulfield, Jay; Hoffman, Adam; McGinn, Michelle K.; Miller-Young, Janice; Haigh, Martin (Teaching and Learning Inquiry, 2013)
The authors propose a working definition of ethical Scholarship of Teaching and Learning (SoTL), advance an ethical framework for SoTL inquiry, and present a case study that illustrates the complexity of ethical issues in SoTL. The Ethical SoTL Matrix is a flexible framework designed to support SoTL practitioners, particularly in the formative stages of their inquiries. Three dominant ethical traditions form the basis of the matrix: teleological or pragmatic, external, and deontological. The key message of the paper is that SoTL practitioners should reflect on different perspectives in their efforts to do what is right in any given situation. The matrix introduces three dominant ethical traditions, but SoTL practitioners may ultimately move beyond these traditions to explore a range of ethical considerations appropriate to their projects and disciplines.